Isolation, identification, and whole-genome sequencing of Streptomyces rochei FE-3-1 against Pyricularia oryzae - Dongxia Du; Zhuo Yi; Shiping Shan; Shuaishuai Gao; Mengyuan Yu; Bin Wang (PLoS ONE, 2025)
Streptomyces are significant producers of antimicrobial secondary metabolites. In this study, a Streptomyces rochei FE-3–1was isolated from the rhizosphere of rice plants, and its metabolites exhibited potent antagonistic activity against plant pathogen Pyricularia oryzae . However, the genome sequence of the strain has not been reported to date. Whole genome sequencing and genome mining were conducted to comprehensively characterize the strain’s main features. The results showed that the total size of the genome is 8,247,561 bp with 72.51% G + C content. Among a total of 7158 genes, 169 predicted RNA genes were identified including 67 transfer RNA (tRNA) genes, 18 ribosomal RNA (rRNA) genes and 84 small RNA (sRNA) genes, as well as 14 genomic islands were predicted. A total of 31 biosynthetic gene clusters were detected within the genome of Streptomyces rochei FE-3–1, and at least four of these gene clusters are associated with known potent antimicrobials. These findings provide a solid theoretical foundation for utilizing strain FE-3–1 in developing biofertilizers or biopesticides within the field of biotechnology.